To what extent does explicit grammatical knowledge in pupils’ mother tongue have an impact on the grammatical understanding of a foreign language? - Riley, Laura (2016)
This is an investigation into the extent to which explicit grammatical knowledge in the mother tongue plays a part in the understanding of grammar in a foreign language. This includes a review of the relevant literature focusing on the differences between explicit and implicit grammatical knowledge alongside studies that have investigated the effects of explicit grammar teaching on the grammatical understanding of a foreign language. Due to time constraints, the research was based on an isolated study using twelve non-native Key Stage three learners of German from various countries who had been learning the language for between four and eighteen months. The research took the form of two questionnaires (initial and reflection questionnaires) and three group discussions. The participants completed tasks identifying different tenses and explaining their formation whilst comparing them with their own language. Each task increased in difficulty, but built upon the knowledge learnt from the previous task. Due to various limitations, no concrete conclusions could be drawn but the study allowed the topic to be explored. However, amongst those who contributed most in the study, the participants with prior L1 grammatical knowledge were able to explain grammar points more clearly than those who did not. In addition, the investigation has identified areas for further research.